Kategoria przyimka jako obiekt opisu lingwistycznego (w związku z międzynarodowym projektem badawczym Przyimki słowiańskie w synchronii i diachronii: morfologia i składnia) - Lachur, Czesław (Acta Polono-Ruthenica, 2006)
The very state of contemporary linguistics presupposes not only the appearance of new aspects and objects of research, but also a return to certain previously described linguistic categories. Preposition is undoubtedly one of these categories. The necessity to re-examine preposition and its functional equivalents in accordance with new theoretical and practical methodologies and requirements gave rise to the international research project Slavonic Prepositions in Synchrony and Diachrony: Morphology and Syntax. Linguists from Russia Ukraine, Belarus, Bulgaria, Serbia and Poland currently participate in the project. This article presents the assumptions and goals of the said project as well as certain problems concerned with the very description of Slavonic prepositions, particularly from contrastive perspective.